Natural resource conservation in the Maribios uplands of Nicaragua. III. Conceptual framework for incentives - Sharma, P.N (IICA, San José (Costa Rica), 2020)
Considerable work has been done on conservation incentives, but a simple, uniform decision-making criterion is still lacking. This paper develops a decision-making tool in the form of a three-part conceptual framework for establishing incentives for different type of farmers. Structural adjustment incentives (e.g., market pricing mechanisms), often needed by medium- and large-scale farmers, are not considered in this analysis. The three dimensions of the incentive problem are: types of farmers, conservation activities to be implemented, and the time frame and quantity of on-site net benefits generated by them. The frameworks helps to conceive and analyze the dimensions, and make a decision regarding incentives. A table containing the results for the three dimensions for each type of farmer is produced. The decision on incentives to be offerred are based on estimates of the on-site net benefits generated by them. The conceptual framework was applied to the Maribios uplands of Nicaragua and incentives for their conservation were developed. The framework can be used for public lands as well as pastures, forested lands and protected areas.